Effects of concrete strength and steel reinforcement area on the mechanical performance of functionally graded reinforced concrete beams: experimental and numerical investigation - Seleem S. E. Ahmad; Esraa Ali; Hesham Elemam; Mohamed Moawad (Fracture and Structural Integrity)
In this work, an experimental and numerical program was designed to evaluate the role of compressive strength, Fc, and area of reinforcing steel, As, on the flexural behavior of functionally graded reinforced concrete beams. Eighteen layered sections of reinforced concrete beams were tested with different compressive strengths arrangement and area of main steel. The result showed that the minimum steel reinforcement with higher compressive strength in the compression zone increases load capacity and ductility up to 31.3% and 37.1% respectively. The average steel reinforcement with higher strength in the compression zone increases load capacity and decreases ductility. The increase in load capacity was 8.3% and the decrease in deflection was 30.3%. The results also approved that; higher strength in the compression zone can be used in beams with a high tensile steel ratio for decreasing compression steel as an economic side. 3D finite element was executed using ABAQUS to simulate experimental beams. The numerical and experimental results in the present work showed a similar behavior but there are slight differences between their values.